RESEARCH AND DEVELOPMENT (R&D) - M Kamal (Al-Afkar : Jurnal Keislaman & Peradaban, 2019)
The fact that occurred in MAN Insan Cendekia Jambi based on observations, many students still had very difficult learning Arabic, this is indicated by the number of students who took the Daily Assessment (PH) which was held at the end of one Basic Competency (KD) or several KD from each semester still ranges between 33-38% of students whose grades reach or are above the Minimum Mastery Criteria (KKM) set. While the remaining 62-67% have not yet reached the KKM. The phenomenon is basically influenced by many factors, including: 1) the learning process that is not going well and not smoothly caused by lack of appropriate and adequate learning resources; 2) teaching materials used are not relevant to students' abilities and conditions 3) teaching materials that do not meet the content and curriculum standards; in the end the teacher is "confused" in choosing the right book or teaching material according to the students' potential and learning needs; 4) Students get bored quickly due to the design of less innovative teaching materials whose presentation does not involve them directly to do the tadribat / drilling or practice exercises.Teaching materials based on tadribat Arabic language developed through Reasearch and Development (R&D) activities are assumed to increase the effectiveness of learning, motivate student interest in learning, and increase student competence. The development of this teaching material is limited to Arabic lessons in class X semester I Madrasah Aliyah which are then designed with due regard; a) material in accordance with Core Competencies (KI) and Basic Competencies (KD), b) material reinforced with vocabulary notation (mufrodat), mahfudhat (Memorization) tashrif lughawy, including interesting pictures related to the lesson, c) exercises (tadribat/drill) varies.